Faktor Faktor yang Berhubungan dengan Stres Kerja pada Pegawai Sekertariat Jenderal Dewan Perwakilan Rakyat Republik Indonesia - Entin Sumartini; Ernyasih Ernyasih (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study aims to identify factors associated with work stress among employees of the Secretariat General of the Indonesian House of Representatives, particularly individual characteristics, workload, and social support. This study uses a cross-sectional design with a quantitative approach. The study sample consisted of 370 employees of the Secretariat General of the Indonesian House of Representatives, selected using stratified random sampling. Data analysis was conducted using the Chi-Square test for bivariate analysis and logistic regression for multivariate analysis. The results of the study indicate that 53.8% of employees experience high work-related stress. Individual characteristics (age, gender, education, length of service) do not show a significant relationship with work-related stress (p > 0.05). Workload has a very significant and perfect relationship with work-related stress (X² = 370,000; p < 0.001; Cramer's V = 1.000). Social support showed a highly significant negative relationship with work-related stress: support from superiors (OR = 5.65; p < 0.001), support from colleagues (OR = 5.72; p < 0.001), and support from family (OR = 5.89; p < 0.001). Workload is the primary predictor of work-related stress, while social support acts as a protective factor. Individual characteristics do not have a significant impact in the context of the Indonesian House of Representatives, indicating the dominance of situational factors. Recommendations: The implementation of a real-time workload monitoring system, supportive supervisor development programs, and strengthening social support through team-building activities and Employee Assistance Programs are needed to reduce work-related stress among employees.